Attention deficit-hyperactivity disorder, comorbidities, and risk situations - Marcelo C. Reinhardt; Caciane A.U. Reinhardt (Brazilian Society of Pediatrics, 2013)
Objective: Attention deficit/hyperactivity disorder (ADHD) is highly prevalent, and its symptoms often represent a significant public health problem; thus, the aim of this study was to verify emergency situations caused by certain comorbidities, or by exposing the patient to a higher risk of accidents. Data source: A literature search was carried out in the PubMed database between the years 1992 and 2012, using the key words "adhd", "urgency", "comorbidity", "substance disorder", "alcohol", "eating disorder", "suicide", "trauma", "abuse", "crime", "internet", "videogame", "bullying", and their combinations. The selection considered the most relevant articles according to the scope of the proposed topic, performed in a non-systematic way. Data synthesis: Several situations were observed in which ADHD is the most relevant psychiatric diagnosis in relation to its urgency, such as the risk of accidents, suicide risk and addition, exposure to violence, or risk of internet abuse or sexual abuse; or when ADHD is the most prevalent comorbidity and is also correlated with emergency situations, such as in bipolar and eating disorders. Conclusions: The results show several comorbidities and risk situations involving the diagnosis of ADHD, thus reinforcing the importance of their identification for the adequate treatment of this disorder.